Effect of Eccentric Isometric Exercises on Developing Legs Muscle Endurance and 800m Running Performance in Youth - Faraj, Abdullah Shanta; Jabbar, Ansam Khazaal (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to enhancing muscle strength, particularly endurance, to achieve the desired 800-meter running feat through the use of appropriate and effective exercises that address muscle contraction in the direction of movement, as in eccentric isotonic exercises. Materials and methods. To achieve the research objectives and address the problem, the researcher used the experimental method with an equivalent control and experimental group design. The researcher defined the research population as (10) youth runners (800 meters) at Al-Qurna Sports Club. Then the sample was selected, which amounted to (8) players, and (2) players were excluded due to the achievement achieved, which affects homogeneity and equivalence. The sample was divided randomly into two groups, a control and an experimental group, with (4) players for each group. Results. Results of research showed that there was an improvement for the control and experimental groups in the research variables, especially the strength endurance of the legs and the achievement in running (800 meters). This is evidence of the success of the exercises used for both groups, which achieved the objectives of the training used. Conclusion. This study found Eccentric isotonic exercises achieved the training goal of developing leg muscle endurance and completing the 800-meter run for young men. It was recommended that Eccentric isotonic exercises be adopted because they achieved the training goal of developing leg muscle endurance and completing the 800-meter run for young men.